2003
DOI: 10.1016/s0741-5214(03)00312-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating effects of method of administration on Walking Impairment Questionnaire

Abstract: The modified WIQ demonstrated good reliability and validity with both methods of administration. These results suggest that the self-administered and telephone-administered versions of the WIQ can be used reliably and efficiently in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 20 publications
2
77
0
Order By: Relevance
“…Average scores obtained on the WIQ subscales in patients with OA are slightly higher than those reported by patients with PAD and lower than those without PAD [13][14]21,[32][33][34][35][36][37][38][39]. In patients with PAD, scores on the walking distance subscale ranged from 25 to 56 [13][14][32][33][34][35]37,39], with most scores clustering at 40 or lower. In patients whose lifestyle was limited by decreased circulation to their legs or who were awaiting surgery, scores were lower, ranging from 3.1 to 12.6 [36,38].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Average scores obtained on the WIQ subscales in patients with OA are slightly higher than those reported by patients with PAD and lower than those without PAD [13][14]21,[32][33][34][35][36][37][38][39]. In patients with PAD, scores on the walking distance subscale ranged from 25 to 56 [13][14][32][33][34][35]37,39], with most scores clustering at 40 or lower. In patients whose lifestyle was limited by decreased circulation to their legs or who were awaiting surgery, scores were lower, ranging from 3.1 to 12.6 [36,38].…”
Section: Discussionmentioning
confidence: 72%
“…The scores are in the upper range of PAD patients and well below those reported by patients without disease. Likewise, patients with decreased circulation to the legs scored between 30 and 39 [13][14][32][33][34][35]37,39] on the walking speed subscale, with severely limited PAD patients scoring between 4.6 and 22.0 [36,38]. Subjects without disease reported scores ranging from 60 to 64 [32,35].…”
Section: Discussionmentioning
confidence: 99%
“…The Walking Impairment Questionnaire (WIQ ) was developed and validated specifi cally for patients with claudication to assess treatment eff ects on claudication-limited walking ability [10].…”
Section: Walking Impairment Questionnairementioning
confidence: 99%
“…Each subscale ranged from 0 % to 100 %, calculated by the score of the respective domain divided by the maximum score of the domain multiplied by 100. The total score was defi ned as the mean of the three subscores [10].…”
Section: Walking Impairment Questionnairementioning
confidence: 99%
“…6,7 However, these ques- However, only Conley et al have evaluated the effects of the two methods of administering the WIQ. 8 Thus, while some studies (not on IC) have shown differences between administration formats, [9][10][11][12] others have found no statistically significant differences. [13][14][15][16][17] For these reasons, in some epidemiological studies, self-administered and interviewer-led questionnaires are available to accommodate the preferences, physical impediments or literacy of the participants.…”
Section: Introductionmentioning
confidence: 99%